AN ANALYSIS OF COOPERATIVE PRINCIPLES IN A GROUP OF MIDDLE-AGED WOMEN CONVERSATION FOUND IN SALAYO WEDDING COOKING TRADITION: A SOCIOPRAGMATIC STUDY - Lesmana, Sabtra; Kharismadewi, Yonnie (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
Communication is a way to interact with others and also a process of delivering information from the speaker to the hearer. As stated that pragmatics is compatible with communicative functions because pragmatics is the study of how language is used in communication. In formal conversations, Grice's cooperative principles are still relevant to apply. The principle of cooperative by Grice is divided into four maxims those are 1) maxim of quality, 2) maxim of quantity, 3) maxim of relevance, 4) maxim of manners. This research is about the principles of cooperative delivered by speakers and hearer related to the data obtained. Therefore, the writers aim to describe the principles of cooperative used in the group of middle-aged women's conversation during the wedding cooking tradition in Salayo. The research is conducted by using a qualitative research methodology. The purpose of this research is to describe the application of the cooperative principles in the conversation of among middle-aged women during the cooking tradition in Salayo. The data used in this study were taken or sourced from a group of middle-aged women's conversation during the cooking tradition in Salayo. In discussing the analysis' results the researchers obtained data in the form of records and field notes, both in the form of descriptions and reflections. The results found in this research are two forms of cooperative principle, those are the maxim of quantity and quality. A number of utterances found are categorized as violations of the maxims if it is based on Grice''s theory, however, that does not apply to the utterances in a group of middle-aged women in Salayo during the cooking tradition. It is because there are social and cultural contexts that must be considered when understanding and analysing these utterances.